Mathematics Communication Skill Seen from Self Efficacy on Project Based Learning Model with Realistic Approach Assisted by Web - Video - Handayani, Kristina; Mariani, Scolastika; Asikin, Mohammad (Unnes Journal of Mathematics Education Research, 2021)
This research aims to describe mathematics communication skill seen from self-efficacy on Project Based Learning model with realistic approach assisted by web-video. This mixed method research used sequential explanatory. The population of this research consisted of VII graders of SMP N 1 Bae Kudus, in academic year 2018/2019. The subjects were VII B students, selected based on three self-efficacy categories: high, moderate, and poor. The techniques of collecting data were mathematics communication skill test, self-efficacy questionnaire, and interview. The findings showed that learning by using PjBL model with realistic approach assisted by web video was effective. The descriptions of the skill seen from self-efficacy of the students within high, moderate, and poor categories on PjBL with realistic approach assisted by web – video were varied on each category. Based on 5 high self – efficacy students, there were 4 of them having high communication skill and 1 moderate communication skill. From 21 students with moderate self – efficacy showed 7 of them having high communication skill, 10 moderate communication skill, and 4 poor skill. From 6 students with poor self-efficacy, there were 2 students with moderate communication skill, and 4 with poor communication skill.